Measurement of the pp̄→Wγ+X cross section at s=1.96 TeV and WWγ anomalous coupling limits - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; et al. (2005)
The WWγ triple gauge boson coupling parameters are studied using pp̄rarr; νγ+X(=e,μ) events at s=1.96 TeV. The data were collected with the D0 detector from an integrated luminosity of 162pb-1 delivered by the Fermilab Tevatron Collider. The cross section times branching fraction for pp̄→W(γ)+X→ νγ+X with ETγ>8 GeV and ΔR γ> 0.7 is 14.8±1.6(stat)±1.0(syst) ±1.0(lum)pb. The one-dimensional 95% confidence level limits on anomalous couplings are -0.88<Δκγ<0.96 and -0. 20<λγ<0.20. © 2005 The American Physical Society.